Rating Communication in GP Consultations: The Association Between Ratings Made by Patients and Trained Clinical Raters - Burt, Jenni (Med Care Res Rev, 2016)
Patient evaluations of physician communication are widely used, but we know little about how these relate to professionally agreed norms of communication quality. We report an investigation into the association between patient assessments of communication quality and an observer-rated measure of communication competence. Consent was obtained to video record consultations with Family Practitioners in England, following which patients rated the physician’s communication skills. A sample of consultation videos was subsequently evaluated by trained clinical raters using an instrument derived from the Calgary-Cambridge guide to the medical interview. Consultations scored highly for communication by clinical raters were also scored highly by patients. However, when clinical raters judged communication to be of lower quality, patient scores ranged from “poor” to “very good.” Some patients may be inhibited from rating poor communication negatively. Patient evaluations can be useful for measuring relative performance of physicians’ communication skills, but absolute scores should be interpreted with caution.